2006
DOI: 10.1111/j.1365-2125.2006.02658.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a single dose of 20 mg tadalafil, a phosphodiesterase 5 inhibitor, on ambulatory blood pressure in subjects with hypertension

Abstract: Aims To test the non‐inferiority of a single dose of tadalafil 20 mg compared with placebo with respect to 26‐h mean ambulatory systolic and diastolic blood pressure in treated and untreated hypertensive subjects. Methods A multicentre, randomized, double‐blind, placebo‐controlled crossover study in 114 subjects with hypertension (36 subjects on no therapy with daytime mean ambulatory blood pressure ≥ 140/85 mmHg; 38 subjects on two to four classes of antihypertensive agents with daytime mean ambulatory blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Their safety and appropriate use was reviewed in the second Princeton Consensus Conference recommendations, 2 and more recent analyses of placebo-controlled and postmarketing surveillance data have demonstrated no new concerns regarding cardiovascular events. 108,109 In fact, a variety of studies have demonstrated a potential role for PDE5 inhibition in the management of hypertension [110][111][112][113] and endothelial dysfunction [114][115][116] in patients at risk for CVD. Effects on endothelial function are believed to underlie the beneficial effect of PDE5 inhibition in patients with pulmonary hypertension, for which sildenafil and tadalafil are licensed for use.…”
Section: Mayo Clinic Proceedingsmentioning
confidence: 99%
“…Their safety and appropriate use was reviewed in the second Princeton Consensus Conference recommendations, 2 and more recent analyses of placebo-controlled and postmarketing surveillance data have demonstrated no new concerns regarding cardiovascular events. 108,109 In fact, a variety of studies have demonstrated a potential role for PDE5 inhibition in the management of hypertension [110][111][112][113] and endothelial dysfunction [114][115][116] in patients at risk for CVD. Effects on endothelial function are believed to underlie the beneficial effect of PDE5 inhibition in patients with pulmonary hypertension, for which sildenafil and tadalafil are licensed for use.…”
Section: Mayo Clinic Proceedingsmentioning
confidence: 99%
“…Five different isozymes of PDE are found in vascular smooth muscle: PDE1, which hydrolyzes preferentially cGMP and is Ca 2+ /calmodulin‐dependent; PDE2, a cGMP‐stimulated phosphodiesterase; PDE3 that hydrolyzes cAMP and is inhibited by cGMP; PDE4, cAMP‐specific phosphodiesterase; and PDE5 that hydrolyzes cGMP and is insensitive to Ca 2+ ‐calmodulin [8,9]. Thus, PDE inhibitors have considerable therapeutic utility for arterial hypertension, pulmonary hypertension, and erectile dysfunction by causing relaxation of smooth muscle [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…4 Acute BP reductions have also been observed after single-dose administration of sildenafil (50 mg) or tadalafil (20 mg) when measured with ABPM. 5,6 Of particular relevance to our study of PF-00489791 is a study of multiple-dose administration of sildenafil in untreated hypertensive patients. 7 In that study, 50 mg of sildenafil or placebo was administered 3 times daily for 16 days in 25 subjects, in a crossover design.…”
Section: Bp Lowering Effectsmentioning
confidence: 99%